Developing the electronics industry - World Bank.; Wellenius, Bjorn; Miller, Arnold; Dahlman, Carl J. (Washington, D.C.: World Bank, 1993)
This book examines the important interrelated issues involving market, technology, manufacturing, distribution, sourcing, and public policy that directly affect key players in the global arena of the electronics industry.
Papers selected from a resident seminar in Washington, D.C., organized by the World Bank.
Includes bibliographical references.
ne 27/04/2018
Loans
Keywords: Electronic industries; Industrialised economic